Going Concern Analysis of Local Coffee Shops in Bukittinggi: A Case Study of VOCA and TenOfTen - Alfihta, Rahmadhani; Yessi, Yessi; Maresti, Dwilla (The Future of Education Journal, 2026)
This study analyzes non-financial factors influencing the going concern condition of two local coffee shops in Bukittinggi City, namely VOCA Coffee and TenOfTen Coffee. The primary focus is on indicators of customer loyalty, supply chain management, adaptability to changing trends, and operational resilience. The research employs a qualitative case study method with a descriptive approach. Primary data were collected through in-depth interviews with the managers of each coffee shop, questionnaires administered to 60 customers, as well as observations and documentation of operational activities. Data analysis was conducted thematically to evaluate how each non-financial indicator supports business continuity. The findings indicate that customer loyalty and adaptation to market trends are the most dominant factors in maintaining the going concern of both coffee shops. TenOfTen Coffee excels in customer loyalty and operational resilience due to its strong base of loyal customers and the availability of backup infrastructure (generators and inventory). Meanwhile, VOCA Coffee demonstrates strengths in product variety and a unique in-store experience. Both coffee shops exhibit relatively effective supply chain management; however, TenOfTen relies more heavily on local suppliers, resulting in a lower risk of delivery delays. These findings underscore the importance of intangible assets (brand, customer experience, and innovation) and relationships with local stakeholders for business sustainability (Putu D. P. Paramitha & Yuniarta, 2024; Riswanto et al., 2024). As recommendations, VOCA Coffee is advised to strengthen customer loyalty programs (e.g., membership schemes or reward points), explore alternative local suppliers, and prepare backup infrastructure (generators and internet connectivity). TenOfTen Coffee should continue to enhance its brand image through digital marketing while maintaining product quality.